Efektivitas Game Edukasi Matematika Berbasis Android dan Desktop untuk Meningkatkan Kemampuan Kognitif Siswa - Syahbudin,; M. Hasrul H,; Ridwang, (Jurnal INSYPRO (Information System and Processing), 2024)
The integration of technology in education, especially through educational games, has emerged as an alternative approach to motivating students, particularly those with special needs, to learn. In this research, a mathematics educational game was designed and implemented on both Android and desktop platforms to assess its impact on the cognitive abilities of students in special education (SLB). The study utilized a quasi-experimental method, with one group of students using the educational game and a control group using traditional teaching methods. Statistical analysis was applied to compare cognitive improvements between the two groups. The findings revealed that students who used the mathematics educational game on Android and desktop showed significantly greater cognitive gains compared to those taught using conventional methods. This suggests that educational games can be a powerful tool for enhancing mathematics learning in special needs students by improving conceptual understanding, critical thinking, and problem-solving skills. The results highlight the importance of further developing and implementing educational games in special education to support cognitive growth. Therefore, technology-driven educational games can significantly enhance learning quality and offer a more interactive and enjoyable educational experience for students